Hepatic vein resection and reconstruction for liver malignancies: expanding indication and enhancing parenchyma-sparing hepatectomy. Issue 6 (12th January 2022) - Kawano, Fumihiro; Mise, Yoshihiro; Yamamoto, Junji; Oba, Atsushi; Ono, Yoshihiro; Sato, Takafumi; Inoue, Yosuke; Ito, Hiromichi; Takahashi, Yu; Saiura, Akio
Abstract : The short-term outcomes after hepatic vein reconstruction (HVR) were evaluated in 41 patients. HVR can be performed safely using autologous vein graft. HVR can increase the functional remnant liver volume, facilitating parenchyma-sparing one-step hepatectomy as well as expanding resectability even in patients with all major hepatic veins involved.